FindMyApps eHealth intervention improves quality, not quantity, of home tablet use by people with dementia - Neal, David P.; Kuiper, Leanne; Pistone, Daniela; Osinga, Channah; Nijland, Sanne; Ettema, Teake; Dijkstra, Karin; Muller, Majon; Dröes, Rose-Marie (Frontiers in Medicine, 2023)
FindMyApps is a tablet-based eHealth intervention, designed to improve social health in people with mild dementia or mild cognitive impairment. FindMyApps has been subject to a randomized controlled trial (RCT), Netherlands Trial Register NL8157. Following UK Medical Research Council guidance, a mixed methods process evaluation was conducted. The goal was to investigate the quantity and quality of tablet use during the RCT, and which context, implementation, and mechanisms of impact (usability, learnability and adoption) factors might have influenced this. For the RCT, 150 community dwelling people with dementia and their caregivers were recruited in the Netherlands. For the process evaluation, tablet-use data were collected by proxy-report instrument from all participants’ caregivers, FindMyApps app-use data were registered using analytics software among all experimental arm participants, and semi-structured interviews (SSIs) were conducted with a purposively selected sample of participant-caregiver dyads. Quantitative data were summarized and between group differences were analyzed, and qualitative data underwent thematic analysis. There was a trend for experimental arm participants to download more apps, but there were no statistically significant differences between experimental and control arm participants regarding quantity of tablet use. Qualitative data revealed that experimental arm participants experienced the intervention as easier to use and learn, and more useful and fun than control arm participants. Adoption of tablet app use was lower than anticipated in both arms. A number of context, implementation and mechanism of impact factors were identified, which might explain these results and may inform interpretation of the pending RCT main effect results. FindMyApps seems to have had more impact on the quality than quantity of home tablet use.